1999
DOI: 10.1071/ea99053
|View full text |Cite
|
Sign up to set email alerts
|

Broccoli yield and quality can be determined by cultivar and temperature but not photoperiod in south-east Queensland

Abstract: Summary. Understanding of genotype and environment interactions will help farmers optimise broccoli (Brassica oleracea L. var. italica Plenck) yield and quality, by matching cultivars to time of sowing. Limited information is available on the effect of temperature and photoperiod on broccoli yield and quality. The objective of this study was to quantify the temperature and photoperiod responses of yield and quality attributes in a subtropical environment. Three cultivars (‘Fiesta’, ‘Greenbelt’ and ‘Marathon’) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The broccoli cultivars selected for the study differed significantly in terms of the nutrient content; it was similar to the values reported in other studies [44,45]. In our own research, changes during storage also occurred in the sugar content.…”
Section: Discussionsupporting
confidence: 85%
“…The broccoli cultivars selected for the study differed significantly in terms of the nutrient content; it was similar to the values reported in other studies [44,45]. In our own research, changes during storage also occurred in the sugar content.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, Thapa et al (2016) reported that the head size changed according to the boron doses and the highest head diameter (21.67 cm) was obtained in 18 kg ha −1 boron application. Additionally, Tan et al (1999) reported that the head diameter in broccoli was between 9.3 cm and 12.4 cm.…”
Section: Resultsmentioning
confidence: 99%
“…The inflorescence production of broccoli cultivars of the Ramoso and Cabeça groups in the hot and humid conditions of Central Amazonia varied between the different cultivars evaluated, in qualitative and quantitative terms, showing the effect of the genotype of each cultivar (TAN et al, 1999).…”
Section: Resultsmentioning
confidence: 97%